DNA sequence of Rhizobium trifolii nodulation genes reveals a reiterated and potentially regulatory sequence preceding nodABC and nodFE. - Schofield, P R (1986)
The Rhizobium trifolii nod genes required for host-specific nodulation of clovers are located on 14 kb of Sym (symbiotic) plasmid DNA. Analysis of the nucleotide sequence of a 3.7 kb portion of this region has revealed open reading frames corresponding to the nodABCDEF genes. A DNA sequencing technique, using primer extension from within Tn5, has been used to determine the precise locations of Tn5 mutations within the nod genes and the phenotypes of the corresponding mutants correlate with their mapped locations. The predicted nodA and nodB genes overlap by four nucleotides and the nod F and nodE genes overlap by a single nucleotide, suggesting that translational coupling may ensure the synthesis of equimolar amounts of these gene products. The nodABC and nodFE genes constitute separate transcriptional units and each is preceded by a conserved 76-bp sequence which may be involved in the regulation of expression of these genes.